Protein kinase A-induced phosphorylation at the Thr154 affects stability of DJ-1. (September 2019) - Ko, Yeon Uk; Kim, Su-Jeong; Lee, Juhyung; Song, Min-Young; Park, Kang-Sik; Park, Jun Bae; Cho, Hyun-Soo; Oh, Young J.
Abstract: Introduction: Most cases of Parkinson's disease (PD) are sporadic, but genetic variations have been discovered in PD patients. PARK7/DJ-1 is a known cause of early-onset autosomal-recessive PD and is implicated in neuroprotection against oxidative stress. Although several post-translational modifications of DJ-1 have been proposed, phospho-modification of DJ-1 and its functional consequences have been less studied. Methods: Putative phosphorylation sites of DJ-1 were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS analysis). Subsequently, phosphorylation site of DJ-1 was confirmed by in vitro kinase assay and cell-based pull-down assay. Impaired dimer formation of phospho-null mutant was measured using DSS crosslinking assay and immunoprecipitation assay. To evaluate physiological consequences of this event, protein stability of DJ-1 WT and DJ-1 phospho-null mutant were compared using cycloheximide chase assay and ubiquitination assay. Results: Here, we showed that DJ-1 directly bound to the catalytic subunit of protein kinase A (PKAcα). We found that PKAcα is responsible for phosphorylation of DJ-1 at the T154 residue. Interestingly, dimerization of DJ-1 was not detected in a DJ-1 T154A mutant. Furthermore, stability of the DJ-1 T154A mutant was dramatically reduced compared with that of wild-type DJ-1. We found that DJ-1 T154A was prone to degradation by the ubiquitin proteasome system (UPS). Conclusion: We identified a novel phosphorylation site of DJ-1. Furthermore, we determined protein kinase A that is responsible for this posttranslational modification. Finally, we demonstrated physiological consequences of this event focusing on dimerization and protein stability of DJ-1. Highlights: PKAcα phosphorylates PARK7/DJ1 at the Thr154 residue. Disruption of Thr154 phosphorylation is linked to a lower stability.